Developing molecular tools to improve grapevine resilience against pathogens: new insights on the role of chloroplasts lipids - Coelho, Sara Domingos (2024)
Tese de mestrado, Biologia Molecular e Genética, 2024, Universidade de Lisboa, Faculdade de Ciências